A Graphene Oxide Nanosheet Supported NHC–Palladium Complex as a Highly Efficient and Recyclable Suzuki Coupling Catalyst - Qian, Yingjie; So, Jaeil; Jung, Sang-Yung; Hwang, Sosan; Jin, Myung-Jong; Shim, Sang Eun (Synthesis, 2019)
A practical heterogeneous catalyst was prepared by anchoring a triazine-tethered N-heterocyclic carbene (NHC)–palladium complex on the surface of graphene oxide (GO) nanosheets. The immobilized complex was characterized by X-ray photoelectron spectroscopy, field-emission transmission electron microscopy, energy-dispersive X-ray spectroscopy, and surface area analysis. It proved to be a highly active and durable heterogeneous catalyst for Suzuki coupling reactions. At room temperature, the use of this catalyst enabled the preparation of various biaryls and heterobiaryls in short reaction times. The catalytic system could be recycled at least 10 times with almost consistent activity. The results reveal that the stable palladium complex is strongly anchored on the surface of GO nanosheets. Interestingly, an open planar network of the GO nanosheet support plays a role during the catalytic process in enhancing the catalytic activity.
Keywords: graphene oxide; palladium; immobilization; heterogeneous catalysis; Suzuki coupling